Effect of advanced chronic kidney disease in clinical and echocardiographic outcomes of patients treated with MitraClip system. (1st November 2015) - Estévez-Loureiro, Rodrigo; Settergren, Magnus; Pighi, Michele; Winter, Reidar; D'Allara, Gianni; Jacobsen, Per; Sondergaard, Lars; Cheung, Gary; Ghione, Matteo; Ihlemann, Nikolaj; Moat, Neil E.; Price, Susanna; et al.
Abstract: Background: Data regarding the influence of different levels of renal dysfunction on clinical and echocardiographic results of MitraClip therapy are scarce. We aimed to evaluate the impact of baseline advance renal failure in the outcomes of a cohort of patients treated with MitraClip. Methods and results: We analyzed data from a multicenter registry of 173 patients treated with MitraClip between 2009 and 2012. Patients were classified as advanced chronic kidney disease (CKD, creatinine clearance [CrCl] < 30 ml/min, group 1, n = 20), moderate CKD (CrCl 30–60 ml/min, group 2, n = 78) and normal renal function (CrCl > 60 ml/min, group 3, n = 75). Twenty patients (11.5%) presented advanced CKD. Procedural success was equal in the 3 groups (95.0% group 1, 100% in group 2 and 96.0% in group 3, p = 0.180). Post-procedural MR and NYHA class at 1 month (MR ≥ 3 + 5.0% vs. 0% vs. 4.0% p = 0.190 and NYHA > II 40.0% vs. 21.0% vs. 18.3%, p = 0.101) and 6 months (MR ≥ 3 + 0% vs. 13.0% vs. 2.7%, p = 0.330; and NYHA class > II 54.5% vs. 26.9% vs. 25.6%, p = 0.298) did not differ between groups. However, patients in group 1 experienced higher frequency of the composite end-point of mortality or readmission at 16.2 ± 11.1 months of follow-up (HR 4.8, CI 95% 1.1–21.3). Conclusion: Advanced CKD is linked to an excess of cardiac adverse events. This should be judiciously taken into account when selecting patients for MitraClip.